Axial compressive behavior of steel-reinforced reactive powder concrete short columns. (December 2022) - Zhang, Lingfeng; Zhang, Ming; Wang, Kun; Shi, Jinyu; Chen, Weihong; Yan, Kai
Abstract: The conventional steel-reinforced concrete (SRC) composite columns are successfully applied in the construction of high-rise buildings and infrastructures. However, the further application is significantly limited by problems such as large self-weight and poor crack-resistance. In this study, an innovative steel-reinforced reactive powder concrete (SRRPC) column was developed to be a new alternative to the traditional SRC column. Four SRRPC short columns, considering the effect of longitudinal reinforcement ratio, steel shape ratio and transverse stirrup ratio, were axially loaded. It was found that the SRRPC column has sufficient axial compressive strength which considerably increased with the increase of these test parameters. Furthermore, increasing the stirrup ratio can effectively improve the post-peak strength. The numerical parametric analysis showed that the axial compressive strength was mainly affected by the compressive strength of the reactive powder concrete (RPC). The nominal-strength models of the existing specifications (EC 4, ACI 318, JGJ 138 and AISC 360) exhibited large conservation in predicting the axial compressive strength. A confined model was successfully developed and reasonable agreements were found between the experimental and predicted axial compressive strengths.